Formation of an infectious virus-antibody complex with Rous sarcoma virus and antibodies directed against the major virus glycoprotein. - Schlesinger, M J (1976)
Preparations of Rous sarcoma virus (RSV) can form an infectious viral-antibody complex with antibodies raised against the major glycoprotein, gp85, isolated from avian myeloblastosis virus and Prague-RSV subgroup C. Binding of anti-gp85 antibodies to RSV can be demonstrated by the inhibition of focus-forming activity after addition of goat anti-rabbit immunoglobulin and by a shift in density of virions treated with anti-gp85 serum. Group- rather than subgroup- specific regions of viral gp85 appear to be the site of binding for infectious complex.